Bilateral obstetric brachial plexus paralysis: a case report - Çelik, Canan; Kulaklı, Fazıl; Erol, Asiye Mukaddes; Akçay Yalbuzdağ, Şeniz; Hacıoğlu, Kadir (The European Research Journal, 2018)
We aim to report a case with bilateral obstetric brachial plexus paralysis rarely seen after cesarean section. A 28-month-old girl was admitted to our outpatient clinic with weakness in both upper extremities. Shoulders were adducted and internally rotated, elbows were extended with flexion fingers. The 37-year-old mother, fetal breech presentation, premature birth and probably traction forces applied at birth were considered among the risk factors. With this case, it is emphasized that obstetric brachial plexus paralysis occurs rarely bilateral and after cesarean section.